Interpersonal Communication Strategies for Mothers and Infants in Melati Room Care: Building Bonds and Supporting the Recovery Process of High-Risk Infants - Ashlikhatul Fuaddah; Kilau Riksaning Ayu (Universitas Widya Mataram, 2025)
Based on news on the solopos.com page (Saputra, 2022), Central Java Province is the region with the highest infant mortality. In terms of health, infant mortality can be caused by the labor process or the condition of the mother experiencing preeclampsia. In this study, the focus in communication science is to provide an understanding of the importance of maintaining interpersonal communication between mothers and babies being treated in the high-risk infant room. The specific objective of this study is to provide an overview of interpersonal communication and the use of visiting time for mothers who have babies and receive care in the Melati room (high-risk infant care) at Prof. Margono Hospital. To answer the research objective, this study will use a qualitative approach with a descriptive qualitative method. Data collection techniques include in-depth interviews and documentation. The informants in this study are mothers with babies who receive care in the Melati room (high-risk infant care) at Prof. Margono Hospital. The benefit of this study is the availability of information regarding the description of the form/model of interpersonal communication between mothers and babies in the Melati Room. This communication ability is expected to create a close relationship between mother and baby, and the baby can recover more quickly. Keywords: Health Communication; Interpersonal Communication; Mother-Infant.